Ghevond Alishan's Literary Activity Through the Light of Russian Interpretations - Hayryan, Zaruhi; Gasparyan, Luiza (ՀՀ ԳԱԱ)
The history of Russian-Armenian literary relationships is one of the brightest and most significant events of the time. It undoubtedly enhanced the mutual cultural heritage and left a profound mark on the worldview, moral and aesthetic values of Armenian and Russian writers, translators, and literary critics. Since the beginning of the 20th-century Armenian culture, mainly Armenian literature, arouse great interest among such outstanding classics, as M. Gorky, V. Bryusov, A. Blok, O. Mandelstam, A. Bely, A. Akhmatova and others. They only appreciated its aesthetic and stylistic texture but also embarked on the laborious work of translating its best achievements into Russian. Համառոտագիր Ռուս-հայկական գրական հարաբերությունների պատմությունը ժամանակի ամենավառ և ամենանշանակալից երևույթներից է, որն, անկասկած, ամրապնդել է փոխադարձ մշակութային ժառանգությունը և խորապես նպաստել է ինչպես հայ, այնպես էլ ռուս ստեղծագործների և գրականագետների աշխարհընկալմանը: 20-րդ դարասկզբին հայ մշակույթը, մասնավորապես հայ գրականությունը, մեծ հետաքրքրություն առաջացրեց այնպիսի ականավոր դասականների շրջանում, ինչպիսիք են Մ. Գորկին, Վ. Բրյուսովը, Ա. Բլոկը, Օ. Մանդել-շտամը, Ա. Բելին, Ա. Ախմատովան և այլոք: Նրանք ոչ միայն գնահատեցին հայ ստեղծագործողների գեղագիտական և ոճական հյուսվածքը, այլև ձեռնամուխ եղան ռուսերեն թարգմանելու հայկական պոեզիայի լավագույն նվաճումները: История русско-армянских литературных взаимосвязей является одной из ярчайших и значимых страниц в жизни двух народов чтоб несомненноб сыграло роль, в деле сближения и обогащения их культурного наследия, отложив глубокий след на мировоззрении, нравственных и эстетических ценностях как армянских, так и русских писателей, поэтов-переводчиков, литературных критиков. В статье отмечается, что с начала ХХ века армянская культура, в частности, литература, вызывала большой интерес у таких выдающихся мастеров слова, как М. Горький, В. Брюсов, А. Блок, О. Мандельштам, А. Белый, А. Ахматова и другие, которые не только оценили и полюбили ее, но и с большим вдохновением стали переводить лучшие ее достижения на русский язык.
Keywords: Review